Spirocyclic Hybrids of Nortropane and 1,3-Oxazinan-2-one Fragments - Mandzhulo, Alexandr; Vashchenko, Iryna; Lukin, Oleg; Shishkina, Svetlana; Dolgonos, Grygoriy; Gerasov, Andrii; Yepishev, Vitaliy; Samofalova, Dariia; Fetyukhin, Volodymyr; Shivanyuk, Alexander (Synthesis, 2024)
We report facile and versatile procedures for the synthesis of exo- and endo-isomeric spirocyclic hybrids of pharmacophoric (1R,5S)-8-azabicyclo[3.2.1]octane (nortropane) and 1,3-oxazinan-2-one fragments. Our approach consists of the hydrocyanation of endo- and exo-isomeric N-Cbz-protected nortropane-3-spiroepoxides, the reduction of hydroxy nitriles into amino alcohols, the synthesis of N-alkylated amino alcohols via reductive amination, the spirocyclization of the amino alcohols, N-alkylation of the unsubstituted 1,3-oxazinan-2-one fragment in the spiro compounds, and removal of the Cbz protecting groups.
Keywords: nortropane; 1,3-oxazinan-2-one; oxiranes; hydrocyanation; reduction; reductive amination; spirocyclization; alkylation